Efficacy of pasteurization and freezing on the inactivation of bovine leukosis virus present in milk - Sandoval Monzon, Rocio Silvia (2020)
The aim of this work was to evaluate the efficacy of pasteurization and freezing on the inactivation of the bovine leukosis virus present in milk. A bioassay was carried out using 16 sheep. The animals received an intraperitoneal leukocytes inoculum from cow milk with cells infected with bovine leukosis virus (BVL) previously treated with one of the virus inactivation methods. Four study groups were evaluated: a) control group: milk without prior treatment, b) pasteurization group: milk treated by pasteurization, c) 12-hour freezing group: milk treated by freezing for 12 hours, d) 36-hour freezing group: milk treated by freezing for 36 hours. In the week 10 of the inoculation, all animals (4/4) in the control group and 3/4 of the animals in the 12 h freezing group were seropositive for VLB, while no animal was seropositive (0/4) for VLB in the pasteurization and 36-hour freezing groups. Significant differences were found between the pasteurization and 36-hour freezing groups with respect to the control (p=0.029). The results indicate that the 36-hour freezing or pasteurization process is efficient in inactivating the bovine leukosis virus.